Between People and the State: The Ambivalence of Prime Minister's Rural Development Fellowship in India. (August 2022) - Tripathy, Jyotirmaya; Mahaprashasta, Jogasankar
The Prime Minister's Rural Development Fellowship (PMRDF), a flagship programme of the Ministry of Rural Development to facilitate development programme delivery in districts affected by Maoist violence, was introduced in 2011 and suspended in 2014. Though in a state of limbo at present, PMRDF created a complex template where binaries such as state/people, top-down/participatory and security/development were transcended and new ways of belonging generated, so as to make the developmental state an everyday reality in the lives of people. In this potential of PMRDF as a knowledge field to move beyond developmental platitudes, we encounter the limits of academic vocabulary to adequately capture how development matters on the ground. The article draws from critical literature on the postcolonial developmental state, secondary material on the experience of the PMRD Fellows as well as primary sources drawn from the authors' interaction with a Fellow from Odisha. It is proposed that through PMRDF, the developmental state established its legitimacy by reaching out to people in underdeveloped regions even as it vernacularized its authority and undermined its own bureaucratic institutions. And the Fellows, far from being carriers of state power, and contrary to their representation in available literature, imagined themselves primarily as champions of people in need of development.